Guidelines for periodontal care and follow-up during orthodontic treatment in adolescents and young adults - Levin, Liran; Einy, Shmuel; Zigdon, Hadar; Aizenbud, Dror; Machtei, Eli E. (Journal of applied oral science, 2012)
Aggressive periodontitis is characterized by non-contributory medical history, rapid attachment loss and bone destruction and familial aggregation of cases. Aggressive periodontitis (both localized and generalized) is usually diagnosed in a young population. This is frequently the age that an orthodontic care is provided to this population. The aim of the present paper is to draw guidelines for periodontal evaluation and monitoring prior to and during active orthodontic treatment. Strict adherence to these guidelines as a routine protocol for periodontal examination prior, during and following orthodontic treatment may dramatically decrease the severity and improve the prognosis of patients with aggressive periodontitis in orthodontic clinics.